Development of a Vitamin-A enriched maja blanca using squash - Bustamante, Alfee N (1997)
Vitamin A deficiency is still one of the most important public health problems in the Philippines. It is in this light that interest in vitamin enrichment of food began as a way of alleviating the problem. This three-phase study was therefore undertaken to develop a vitamin A-enriched maja blanca using squash (Cucurbita maxima Duchesne var. Sampuso). In phase I, Guzman's maja blanca formulation was selected from three recipes to serve as control. In phase II A, three maja blanca samples with varying squash levels (40%, 50% and 60%) were prepared and evaluated to determine the most acceptable level of incorporation. Based on sensory evaluation results, 50% level of squash was chosen. In phase II B, three 5-kilogram batches of maja blanca were produced and assessed for reproducibility. Sensory test results showed no significant differences among samples due to the production runs. In Phase III A, maja blanca with squash was found through spectrophotometric method that contain 1166.67 IU or 349.65 RE of vitamin A while the control had none. Physico-chemical tests showed that the basic maja blanca has a water activity of 0.87 and a pH of 6.7 while the enriched, 0.88 and 6.5, respectively. Both formulations have soluble solids (°Bx) contents of 22. The enriched maja blanca has a color corresponding to 2.5y 8/10 while the basic product is neutral with a value of 3. As for the proximate composition, basic maja blanca has 61.93% moisture, 0.99% crude protein, 1.23% crude fat, 0.40% total dietary fiber, 34.70% total available carbohydrates and 0.74% ash whereas the enriched formulation has 60.13%, 0.88%, 1.74%, 0.91%, 35.36% and 0.97%, respectively. In Phase III B, microbial analysis of the basic and the enriched maja blanca showed microbial loads within the standard limit of 5.0 x 10^6 cfu/g. In Phase III C, cost analysis based on 5-kg production batches of both the basic and the enriched maja blanca showed that a 50-g serving portion costs P2.68.